ANALYSIS OF POTENTIAL ENERGY OF SEA WAVES IN SOUTHERN WATERS OF MALANG USING GEOGRAPHIC INFORMATION SYSTEMS APPROACH - Setyawan, Fahreza Okta; Sartimbul, Aida; Fuad, Mochamad Arif Zainul; Ussania, Qoirunnisa; Hidayatullah, Fathurrosyid; Haq, Nuril Annisa (Journal of Environmental Engineering and Sustainable Technology, 2023)
Southern waters of Malang are one of the areas in the south of Java where some of its coastal areas have not been electrified. The purpose of this research is to determine the magnitude of wave energy potential in the waters of South Malang. The theoretical amount of wave energy is obtained through wave data processing (wave period, significant wave height, and wave direction) and the results are in the form of the wave energy value with the highest value in 2021 occurring in August with an average value of 40 kW /m - 50 kW/m while in 2022 the highest value occurs in July with an average value of 40 kW/m to 50 kW/m. The technical potential value of wave energy is calculated by adding the efficiency formula from AquaBuOY so that results with the highest technical wave energy potential value are obtained in 2021 in August with an average value of 40 kW/m - 50 kW/m while in 2022 the highest potential wave energy value occurs in July with an average value of 40 kW/m - 50 kw/m. Potential locations are determined based on theoretical and technical potential results and the suitability of placing AquaBuOY so that a station point that meets these criteria is obtained, namely at the 29, 30, and 34 where station 30 is the station that has the closest criteria to effectively installing buoys with the total theoretical energy is 4838.46 MW and technically it is 4354.61 MW in 2021 while in 2022 the total theoretical energy is 4387.95 MW and technically it is 3977.38 MW.